Meningkatkan Keterampilan Membaca Kritis Buku Teks dalam Belajar Sejarah Melalui Metode Search, Solve, Create and Share (SSCS) - Rita Rosita; Nana Supriatna (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
Students’ critical reading skill is being decreasing, especially in learning history. In the other hand, students’ reading skill during learning history is important and has its significance to be developed. The indications can be seen from the ability on finding and comparing reading sources, analyzing readings, making notes from reading results, and sharing information from reading analysis results. Due to the significance of this research, author formulates some problems taken, those are: first, how to develop history learning using methods Search, solve, create, and share (SSCS). Second, how to implement the search, solve, create, and share methods (SSCS). Third, how to increase learning using the search, solve, create, and share methods (SSCS). Fourth, the efforts to overcome the obstacles arisen in the application of search, solve, create, and share (SSCS) method. This study aims to improve critical reading skills of student's history textbook during learning history. This study uses a classroom action research model with Kemmis and Taggart design consisting of planning, implementation, observation, and reflection. This study aspects of the textbook's Critical reading skills are selecting information from the historical textbook that corresponds to the discussion, finding information from the history textbooks, analyzing the content of the reading in the history textbooks, asking questions to the teacher or friends about the learning materials in the history textbooks, making notes based on the readings from the history textbook, sharing the work based on the reading results. Based on the results, this search, solve, create, and share (SSCS) may improve Students’ critical reading skill in history learning . This is indicated by the increase in the critical reading skill on textbook of the learning process in each cycle.